Circular Economy in the building sector: Three cases and a collaboration tool. (1st March 2018) - Leising, Eline; Quist, Jaco; Bocken, Nancy
Abstract: The Circular Economy (CE) gained significant traction in business and academia. While in the building sector issues around energy efficiency are being widely explored, CE is still a relatively new topic. This article reports on three CE pilots in the Dutch building sector and develops a collaboration tool for developing and operating circular buildings and their supply chain collaborations. First, a conceptual framework is developed to study supply chain collaboration in circular buildings, which uses theoretical building blocks for visions, actor learning, network dynamics and business model innovation. Second, a case study is presented where the framework is applied to three cases using semi-structured interviews and document analysis. Third, an empirically-based tool is developed to enhance collaboration for CE in the building sector. The cases include a newly built project, a renovation project and a demolition project. It was found that developing circular buildings requires (i) a new process design where a variety of disciplines in the supply chain is integrated upfront, (ii) the co-creation of an ambitious vision, (iii) extension of responsibilities to actors along the entire building supply chain, and (iv) new business and ownership models. Highlights: The Circular Economy requires new types of supply chain collaborations. The paper develops a framework for supply chain collaboration in circular buildings. Three cases are studied: a new building, a renovation and a demolition project. Visions, learning, network dynamics and business model innovation are analyzed. A novel collaboration tool for developing circular buildings is developed.